THE IMPACT OF GENERATIVE AI–INTEGRATED TEACHING ON UNIVERSITY STUDENTS’ KEY COMPETENCIES - Min Hui Lee; Linda Lin Chin Lin (International Journal of Application on Economics and Business, 2026)
With the rapid proliferation of Generative AI (GenAI), higher education is facing a critical shift in pedagogical paradigms. This study investigates the impact of integrating GenAI tools—such as ChatGPT, Gemini, and Canva AI—into an undergraduate "Digital Marketing" course on students' key competencies, including problem-solving, critical thinking, and digital marketing proficiency. Utilizing the TPACK (Technological Pedagogical Content Knowledge) framework for instructional design and the SAMR (Substitution, Augmentation, Modification, Redefinition) model for assessing technology integration, this research analyzed data from 48 second- and third-year students. Data collection involved a three-stage Likert-scale survey (Pre-test, Mid-process, Post-test) and qualitative interviews. The findings indicate that GenAI integration significantly enhanced student interest (M=4.28) and self-efficacy. Students reported that AI enabled them to achieve innovative outcomes previously unattainable, aligning with the "Redefinition" level of the SAMR model (M=4.06). Qualitative feedback revealed a cognitive shift where students evolved from "passive consumers" to "strategic analysts" capable of deconstructing cross-platform marketing tactics. However, a significant discrepancy was identified: while students highly rated their ability to evaluate AI content quality (M=4.22), pedagogical observations revealed an "over-reliance" on AI, characterized by a lack of fact-checking and a trend toward content homogenization. The study concludes that while GenAI serves as an effective creative scaffold, future TPACK-based instruction must prioritize "AI Literacy" and "Verification Competencies" to safeguard critical thinking and original creativity in higher education.